The bank lending channel in Peru: a VECM approach - Espinoza Ipanaque, Paul Christian (2020)
It seeks to determine the existence of the bank loan channel in national and foreign currency for Peru during the period from the first quarter of 2010 to the first quarter of 2019. To achieve this objective, time series are used in correction models of VECM errors, following the relationship of a theoretical IS-LM model with the banking sector. Evidence is found that the bank loan channel in national currency would be operating. In turn, foreign exchange reserve funds are good long-term predictors of the level of foreign currency credits, however there is no credit channel in that currency. This research serves to clarify the mechanism of transmission of monetary policy through credit towards economic activity. In addition, it is useful for the design and application of monetary policy. Finally, this is the first paper to use the VECM methodology to study the bank loan channel in Peru. Jel Classification: E51; E52; E58.